2011
DOI: 10.1007/s13337-011-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Rabies in South Indian Cows: An evidence of Sri Lankan Rabies virus Variant Infection Based on the Analysis of Partial Nucleoprotein Gene

Abstract: Rabies is a highly fatal non-suppurative encephalomyelitis, caused by the Rabies virus. Dogs are the major reservoir of rabies in India and are the source of infection to other domestic animals. In this report, laboratory investigation and molecular characterization of isolates from two cows with paralytic rabies is described. Necropsy brain samples from the two cows were tested for the presence of rabies antigen using a fluorescent antibody test and the results were confirmed using RT-PCR. Rabies virus was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The present phylogentic analysis showed that our field rabies isolates were of high nucleotide sequence similarity with each other and with earlier reported Indian sequences by falling into one cluster that confirms that our field rabies isolates belongs to genotype 1 [16], and because of clustering with other reported Indian isolates which are of Arctic like lineage, our isolates also belong to Arctic like lineage. This endorses the findings of Mehta et al [13], Pant et al [17], Jamil et al [8], Reddy et al [18], Arvindhbabu et al [2] and Nagrajan et al [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present phylogentic analysis showed that our field rabies isolates were of high nucleotide sequence similarity with each other and with earlier reported Indian sequences by falling into one cluster that confirms that our field rabies isolates belongs to genotype 1 [16], and because of clustering with other reported Indian isolates which are of Arctic like lineage, our isolates also belong to Arctic like lineage. This endorses the findings of Mehta et al [13], Pant et al [17], Jamil et al [8], Reddy et al [18], Arvindhbabu et al [2] and Nagrajan et al [16].…”
Section: Discussionsupporting
confidence: 90%
“…Reddy et al [18] found that 30 rabies virus isolates from different states of India were genetically closely related with a single cluster under Arctic/Arctic-like viruses. Arvindhbabu et al [2] found that two adult cow isolates belonged to the genetic cluster 3 (GC3) which is restricted to southern India and GC3 was found to be related to Sri Lankan rabies isolates with a strong bootstrap value of 96%. Nagrajan et al [16] showed that RV isolates in Southern India belong to genotype 1 by phylogenetic analysis of the portion of nucleoprotein gene sequence of 22 rabies virus isolates obtained from domestic animals in Southern India.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports had speculated the presence of this distinct Sri Lankan variant in India and suggested that movement of humans and their animals between Sri Lanka and India, particularly within the southeastern coastal area of the mainland, may have resulted in the movement of this variant between these geographically separate regions [ 13 – 15 ]. Other studies confirmed the circulation of this distinct variant found only in Sri Lanka and mostly the southern part of India [ 16 ]. However, recently isolates from Nepal have also been reported to be phylogenetically related to these distinct variants and this lineage has been designated as the Indian subcontinent rabies virus clade [ 17 ].…”
Section: Discussionmentioning
confidence: 58%